UPAYA GURU DALAM MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN FIQIH DI MADRASAH IBTIDAIYAH NEGERI MUKTI KARYA KECAMATAN PANCA JAYA KABUPATEN MESUJI - Aziz, Abdul; Ifrianti, Syofnidah (Universitas Islam Negeri Raden Intan Lampung, 2015)
Teacher is figure and role model to her/his students and environment. That is why a teacher must have certain qualification standards, such as resposibility, authority, independent, and discipline. Teacher of Fiqih subject in MIN Mukti Karya, Panca Jaya, Mesuji had given his best in educating his students. In this case, the teacher had tried to conduct teaching-learning process and motivate his students well. Unfortunately, the result was not optimal yet. Based on those facst, this reasearch was conducted to find out why the teacher’s efforts have not been successful to improve learning achievement in MIN Mukti Karya, Panca Jaya, Mesuji. The writer used observation, interview, and documentation to gain the data. Observation was used to know the real teaching-learning process, interview was used to gain the data of the obstacles faced by the teacher, and documentation was used to know the teacher’s preparations. Data sources of this research were head master, teacher, and students. Finally to analize the data, the writer used data reduction, data display, and conclusion drawing. Based on result of data analisys, the writer concluded that factors which caused teacher’s efforts had not managed to improve students’ achievement were: (1) inadequate learning resources; (2) lack of props and media, (3) lack of supervision, control, and good exemplary done by parents.